“If you want to compose verses, you have to know arguing”. Arguing poetry in son jarocho - Arranz Mínguez, Conrado José (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This work proposes the approaching to the conceptualization of the poetry of argument orarguing’s verses occurring in son jarocho, especially in the region of Los Tuxtlas. In addition,we will analyze its poetic characteristics and the way it develops within the festive ritual. Forthis, we will do an analysis of some of these poems contained in poets’ notebooks, as well ason oral testimonies of these poets, whether they have been collected in books or interviews,that is, we will analyze the poetry in relation to its context. In the dialogism and in the topic ofthis poetry we find two fundamental elements out to understand the dynamics of traditionalizationand innovation that take place in these poetic-musical festive rituals, despite the creativecomponent -sometimes improvised- that depends on the verseros [this kind of poets].